Care coordination across healthcare systems: development of a research agenda, implications for practice, and recommendations for policy based on a modified Delphi panel - Aneesa Motala; Susanne Hempel; Michelle Wong; Maria Bolshakova; Ning Fu; David Ganz; Sonali Saluja; Timothy Kim; Carolyn Turvey; Kristina Cordasco; Aashna Basu; Tonya Page; et al. (BMJ Open)
Objective For large, integrated healthcare delivery systems, coordinating patient care across delivery systems with providers external to the system presents challenges. We explored the domains and requirements for care coordination by professionals across healthcare systems and developed an agenda for research, practice and policy.Design The modified Delphi approach convened a 2-day stakeholder panel with moderated virtual discussions, preceded and followed by online surveys.Setting The work addresses care coordination across healthcare systems. We introduced common care scenarios and differentiated recommendations for a large (main) healthcare organisation and external healthcare professionals that contribute additional care.Participants The panel composition included health service providers, decision makers, patients and care community, and researchers. Discussions were informed by a rapid review of tested approaches to fostering collaboration, facilitating care coordination and improving communication across healthcare systems.Outcome measures The study planned to formulate a research agenda, implications for practice and recommendations for policy.Results For research recommendations, we found consensus for developing measures of shared care, exploring healthcare professionals’ needs in different care scenarios and evaluating patient experiences. Agreed practice recommendations included educating external professionals about issues specific to the patients in the main healthcare system, educating professionals within the main healthcare system about the roles and responsibilities of all involved parties, and helping patients better understand the pros and cons of within-system and out-of-system care. Policy recommendations included supporting time for professionals with high overlap in patients to engage regularly and sustaining support for care coordination for high-need patients.Conclusions Recommendations from the stakeholder panel created an agenda to foster further research, practice and policy innovations in cross-system care coordination.